2b-7(3+6)=6+3

Simple and best practice solution for 2b-7(3+6)=6+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2b-7(3+6)=6+3 equation:


Simplifying
2b + -7(3 + 6) = 6 + 3

Combine like terms: 3 + 6 = 9
2b + -7(9) = 6 + 3

Multiply -7 * 9
2b + -63 = 6 + 3

Reorder the terms:
-63 + 2b = 6 + 3

Combine like terms: 6 + 3 = 9
-63 + 2b = 9

Solving
-63 + 2b = 9

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '63' to each side of the equation.
-63 + 63 + 2b = 9 + 63

Combine like terms: -63 + 63 = 0
0 + 2b = 9 + 63
2b = 9 + 63

Combine like terms: 9 + 63 = 72
2b = 72

Divide each side by '2'.
b = 36

Simplifying
b = 36

See similar equations:

| 4(x-3)=10x-6(x-7) | | 64=16t^2+64t+4 | | 4(m-3)=10x-6(x-7) | | 3x^2+y^2-24x+39=0 | | 50x+50y=800 | | -2(x+5)=5(2-x)+12 | | x-(x*0.5)=2000 | | 3x(x-5)=7(x*x)-16x | | x+10=4x+7 | | 2*x=0 | | (3x+1)=0 | | 7x+37=25x+1 | | c=7.13(3.14) | | (3x+12)=0 | | 9x+20=15x+2 | | -5(3x+6)=15 | | -c^2+24c-82=0 | | 2(x-6)=18 | | (5m^2+m)7m=0 | | y+8=1 | | r+27=22 | | 2*(3x+1)=0 | | A^2+25-10a=0 | | 14(t-5)+7t=7(3t+5)-13 | | 14(t-5)+7t=t(3t+5)-13 | | 20m^2=-2m^3-50m | | -4(-2x+3)=12 | | 4x^2-12x=16 | | 9y-2y=14 | | 2a=2 | | 1.6x=8 | | X^3+24x^2+144x=0 |

Equations solver categories